2022
DOI: 10.3389/fpsyg.2022.898503
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Awareness and Attitudes Toward Threatened Animal Species

Abstract: The preservation of our planet’s decreasing biodiversity is a global challenge. Human attitudes and preferences toward animals have profound impacts on conservation policies and decisions. To date, the vast majority of studies about human attitudes and concern toward animals have focused largely on western, educated, industrialized, rich and democratic (i.e., WEIRD) populations. In order to mitigate biodiversity loss globally, an understanding of how humans make decisions about animals from multicultural persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…But unlike animal abusers, who physically torture animals, the involvement of doghunters in crimes is more difficult to prove. As Kazakh lawyers explain, only the evidence base can help in this, namely, a photo or video recording of the fact of laying out the bait and the found dead animal; the conclusion of a veterinarian about what happened to the animal (Bruder et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…But unlike animal abusers, who physically torture animals, the involvement of doghunters in crimes is more difficult to prove. As Kazakh lawyers explain, only the evidence base can help in this, namely, a photo or video recording of the fact of laying out the bait and the found dead animal; the conclusion of a veterinarian about what happened to the animal (Bruder et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Although studying the influence of the different nationalities on adolescent IA is not possible in our sample, a possible approach to consider in the future is to extend and divide the sample using the regional criteria based on the United Nations Department of Economic and Social Affairs, Statistics Division for use in the Sustainable Development Goals (SDG) indicators. A similar approach was adopted by Bruder et al (2022) in their study on cross-cultural awareness and attitudes towards endangered species. Due to the limited sample size, we did not individually study the difference within the different age groups of adolescent IA and considered them a whole group.…”
Section: Discussionmentioning
confidence: 99%
“…liking animals) in uenced willingness to donate for animal conservation more than economic factors or scienti c considerations, especially among visitors with less knowledge and concern about environmental issues. Similarly, Bruder et al (2022) used a representative survey of citizens and residents in Qatar to examine the relationship between familiarity, liking and support for government protection of endangered animals. The authors found that liking was a strong predictor of support for government protection and that liking mediated the effect of familiarity on support for government protection across cultural groups.…”
Section: Introductionmentioning
confidence: 99%